Gender Power and Family Decision in an Extended Solowian Economic Growth Model - Wei-Bin Zhang, (Technium Social Sciences Journal, 2021)
The purpose of this paper is to deal with dynamic interdependence between economic growth and family-based behavior. The decision unit on consumption and saving is the family which is composed of the husband and the wife. The model endogenously determines national growth, family goods, family wealth, and gender-differentiated consumption and labor supply with fixed distribution of power between the husband and the wife. The model is based on synthesizing a few approaches in economics. The growth mechanism and economic structure are based on a generalized Solowian growth model. The household behavior is based on Zhang’s concept of disposable income and utility. The power distribution is referred to the collective approach by Basu (2006). We first develop the model and study dynamic behavior of the model. We conduct comparative dynamic analyses to demonstrate how economic growth interacts with family behavior by allowing exogenous changes in gender power distribution, gender-based preferences and human capital, and national technological changes.